Предмет: Алгебра,
автор: 111111DA
Весь день решаю,не получается,помогите!
Тема:иррациональные уравнения
Приложения:
Ответы
Автор ответа:
1
(x+2)^2 * (x^2 - x - 20) = 36x^2 + 144x + 144
(x+2)^2 * (x^2 - x - 20) = 36(x^2 + 4x + 4)
(x+2)^2 * (x^2 - x - 20) = 36(x+2)^2
(x+2)^2 * (x^2 - x - 20) - 36(x+2)^2 = 0
(x+2)^2 * (x^2 - x - 20 - 36) = 0
(x+2)^2 * (x^2 - x - 56) = 0
(x+2)^2 = 0
x^2 - x - 56 = 0
x не равняется 2, x = 8, x = -7
(x+2)^2 * (x^2 - x - 20) = 36(x^2 + 4x + 4)
(x+2)^2 * (x^2 - x - 20) = 36(x+2)^2
(x+2)^2 * (x^2 - x - 20) - 36(x+2)^2 = 0
(x+2)^2 * (x^2 - x - 20 - 36) = 0
(x+2)^2 * (x^2 - x - 56) = 0
(x+2)^2 = 0
x^2 - x - 56 = 0
x не равняется 2, x = 8, x = -7
Похожие вопросы
Предмет: Русский язык,
автор: nurajaldabergen1
Предмет: Математика,
автор: vasenkoroman41
Предмет: Қазақ тiлi,
автор: lololpopdpdb
Предмет: Математика,
автор: Братлартуганнар
Предмет: Литература,
автор: deminaveronich